The Press Media as a Place for the Articulation of Discursive Networks: the Case of the Inclusion Law in Chile (Foro de Educacion, 2021)
The Chilean educational system, which is considered an emblem of neoliberal public policies, was subjected to a profound legal refom in 2014. The moderate left-wing government passed the «Ley de Inclusión» bill, which seeked avoiding the selection of students, the charging of copay upon families in publicly financed schools, and ending the possibility that private schools, which received public financing, could seek profit. During the discussion of this bill, a set of educative, political and social actors articulated and mobilized looking to stop this. The purpose of this paper is to identify and describe the argumentative twists present in the discursive community that opposed the «Ley de Inclusión» bill. The corpus used consists of 139 opinion columns, published in «El Mercurio» and «La Tercera», the two main political media papers between March of 2014 and January of 2015. From an analysis ot these argumentative twists, a discursive coalition was built. The beliefs and representations of the educational community condense on: the need for a gradualist and evidence-based public policy; the free choice of schools as the dominant rationality and tool in the educational quasi-market; and the defense of private education as a means to ensure the existence of differentiated and plural educational offers in the educational system.